Finite-temperature spectrum at the symmetry-breaking linear to zigzag transition - Kiethe, Jan; Timm, Lars; Landa, Haggai; Kalincev, Dimitri; Morigi, Giovanna; Mehlstäubler, Tanja (Physical Review B, 2021)
We investigate the normal-mode spectrum of a trapped ion chain at the symmetry-breaking linear to zigzag transition and at finite temperatures. For this purpose, we modulate the amplitude of the Doppler cooling laser to excite and measure mode oscillations. The expected mode softening at the critical point, a signature of the second-order transition, is not observed. Numerical simulations show that this is mainly due to the finite temperature of the chain. Inspection of the trajectories suggest that the thermal shifts of the normal-mode spectrum can be understood by the ions collectively jumping between the two ground-state configurations of the symmetry-broken phase. We develop an effective analytical model, which allows us to reproduce the low-frequency spectrum as a function of the temperature and close to the transition point. In this model, the frequency shift of the soft mode is due to the anharmonic coupling with the high-frequency modes of the spectrum, acting as an averaged effective thermal environment. Our study could prove important for implementing ground-state laser cooling close to the critical point.
Created from Fastlane, Scopus look-up